Fluctuating Geographical Position Within a Geopolitical and Historical Context. Case study: Romania - Sageata, Radu Danut (Geographica Pannonica, 2020)
The geographical position of a territory is a statically element strictly determined by mathematical landmarks and by those of the natural background. For all that, different historical and geopolitical events that happened in the course of time, can make the geographical position fluctuate by including a territory / state into territorial aggregates established on less arbitrary criteria. Thus, many interwar authors placed Romania, by geographical criteria, in Central Europe; after 1945 they would include it in Eastern Europe, or in short, in the East, a political-ideological homogeneous territory, but heterogeneous geographically, historically and cultural. With the downfall of political-ideological barriers and the deep-going mutations in the geopolitics of Central and Eastern Europe, Romania’s geographical position should be reconsidered based on objective criteria: geographical, mathematical and last but not least, cultural and economic. This study is also important because some recent works place Romania erroneously in South-Eastern Europe, either in eastern or in Balkan Europe. The work concludes that Romania in a state situated in the south-eastern part of Central Europe. The arguments brought in favour of it have in view to push forward the current stage of knowledge on Romania’s geopolitics.